A Review on Mining Large Unstructured Datasets to Find Top-K Competitors - Lasya Reddy, B; Salam, Shaik (International Journal of Computer Sciences and Engineering, 2025)
Now-a-days in any business field we are hearing about the word ‘competition’. So, by competitive analysis we can analyze the competitors and can assess the strengths and weakness of a competitor. Competition is necessary in marketing to know which companies are primary competitors and also know which company is competing with itself. So by this we make our products, services and marketing stands out well in business. Competitiveness between two items can be defined based on market segments that they can both cover. Competitiveness is evaluated in large review datasets and address the problem of finding top-k competitors. For evaluating of competitiveness, it utilizes customer reviews which are abundantly available in wide range of domains. There are so many efficient methods for addressing the problem of finding top-k competitors in terms of scalability, accuracy.